High Immunogenicity of a T-Cell Epitope-Rich Recombinant Protein Rv1566c-444 From Mycobacterium tuberculosis in Immunized BALB/c Mice, Despite Its Low Diagnostic Sensitivity - Luan, Xiuli; Fan, Xueting; Wang, Ruihuan; Deng, Yunli; Chen, Zixin; Li, Na; Yan, Yuhan; Li, Xiaoyan; Liu, Haican; Li, Guilian; Wan, Kanglin (Frontiers in Immunology, 2022)
The discovery of immunodominant antigens is of great significance for the development of new especially sensitive diagnostic reagents and effective vaccines in controlling tuberculosis (TB). In the present study, we targeted the T-Cell epitope-rich fragment (nucleotide position 109-552) of Rv1566c from Mycobacterium tuberculosis (MTB) and got a recombinant protein Rv1566c-444 and the full-length protein Rv1566c with Escherichia coli expression system, then compared their performances for TB diagnosis and immunogenicity in a mouse model. The results showed that Rv1566c-444 had similar sensitivity with Rv1566c (44.44% Vs 30.56%) but lower sensitivity than ESAT-6&CFP-10&Rv3615c (44.4% Vs. 94.4%) contained in a commercial kit for distinguishing TB patients from healthy donors. In immunized BALB/c mice, Rv1566c-444 elicited stronger T-helper 1 (Th1) cellular immune response over Rv1566c with higher levels of Th1 cytokine IFN-γ and IFN-γ/IL-4 expression ratio by ELISA; more importantly, with a higher proliferation of CD4+ T cells and a higher proportion of CD4+ TNF-α+ T cells with flow cytometry. Rv1566c-444 also induced a higher level of IL-6 by ELISA and a higher proportion of Rv1566c-444-specific CD8+ T cells and a lower proportion of CD8+ IL-4+ T cells by flow cytometry compared with the Rv1566c group. Moreover, the Rv1566c-444 group showed a high IgG secretion level and the same type of CD4+ Th cell immune response (both IgG1/IgG2a >1) as its parental protein group. Our results showed the potential of the recombinant protein Rv1566c-444 enriched with T-Cell epitopes from Rv1566c as a host T cell response measuring biomarker for TB diagnosis and support further evaluation of Rv1566c-444 as vaccine antigen against MTB challenge in animal models in the form of protein mixture or fusion protein.